Regulation of voltage-gated ion channels by NGF and ciliary neurotrophic factor in SK-N-SH neuroblastoma cells - Lesser, SS (J Neurosci, 1995)
Neurotrophic factors have powerful effects on neuronal differentiation and the maintenance of neuronal phenotype, but understanding of their regulation of one important aspect of neuronal function, excitability, remains limited. We have examined the regulation of voltage-gated ion channels by two unrelated neurotrophic factors, NGF and ciliary neurotrophic factor (CNTF), in the SK-N-SH neuroblastoma cell line that is responsive to both factors. NGF and CNTF have strikingly different neuronal specificities and distributions in the nervous system, and might be expected to have significantly different effects on neuronal function. Using whole-cell, perforated-patch, and single-channel recording, we found that treatment with NGF increased levels of voltage- gated sodium, calcium, and potassium currents. In contrast, CNTF treatment increased levels of potassium currents only. NGF and CNTF appeared to regulate the same delayed-rectifier potassium current; in addition, NGF treatment resulted in increased levels of a second potassium current component. Such differential effects of neurotrophic factors on the expression of voltage-gated ion channels would have profound effects on the excitability of target neurons in vivo.